+0  
 
0
251
1
avatar

5(1+2)^2-4(3-1)^3-6(2+3)^4=???

Guest Feb 10, 2017
 #1
avatar+7068 
+1

5(1+2)^2-4(3-1)^3-6(2+3)^4

 

= 5(3)^2 - 4(2)^3 - 6(5)^4

 

=5(9) - 4(8) - 6(625)

 

= 45 - 32 - 3750

 

= -3737

hectictar  Feb 10, 2017

13 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.